The Influence of Service Quality on Consumer satisfaction Delivery Services at JNT Express in Garut - Nurul Fauziyah Rahmah; Fitriani Nur Utami (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The development of commerce is one of the many factors that drive the development of logistics in Indonesia. The reason for this to happen is due to the large demand for goods delivery services. JNT Express is one of the 2nd most popular shipping services in Indonesia which has a good existence and achievements. Because JNT Express is the most frequently used delivery service, in fact many consumer complaints arise due to the poor implementation of service quality and its impact on customer satisfaction. The high use of delivery services and similar online shop makes delivery services need to pay attention to and improve service quality so that there are no complaints about services so that they get satisfaction and a positive experience in the eyes of consumers. In this research, the aim is to obtain information on "The Influence of Service Quality on Consumer Satisfaction of JNT Express Delivery Services in Garut". This research uses a quantitative method with a causal descriptive approach, using a simple linear regression analysis technique which is then tested using IBM SPSS 25 software. The sampling process is carried out using a non-probability sampling with purposive sampling to 100 respondents. Based on a partial hypothesis test, service quality has a significant impact on customer satisfaction with delivery services at JNT Express in Garut. Based on the coefficient of determination, it is found that service quality can have an influence on customer satisfaction of 62.6% and the remaining 37.4% can be influenced by external factors which are not the focus of this research.